(untitled) (International Journal of Engineering and Computer Science, 2015)
Clustering is one of the significant tasks in data mining which is benevolent for bounteous users by affording analysis and decision making. This paper inaugurates agile and dexterous way to conceive horizontal layout and forthright usage of horizontal layout in data mining algorithms like clustering. Predominantly educing a data set in data mining project for analysis is a time conceiving, striving task so horizontal layouts are created and stored in database which averts the burden of performing data preprocessing in data mining projects .The vertical layouts created by vertical aggregations in SQL are impotent for data mining algorithms so horizontal aggregations are used to create horizontal layouts. It is surpass to create horizontal layout instead of creating vertical layout as vertical layout only creates one column per aggregated group by using normal SQL (Structured Query Language) aggregations and horizontal layouts returns many values per aggregated group or row so they are useful for data mining algorithms. Through CASE and SPJ methods horizontal aggregations are evaluated for creating horizontal layouts dexterously and agilely. This paper induces how horizontal layout can be created easily with CASE method than by using SPJ method. To prepare a data set for clustering takes more time and effort so the created horizontal layout is obliged for clustering directly without wastage of time and effort. As in data uncertainty is the key feature so by using soft computing concepts like Fuzzy Set, clustering of horizontal layout is done, hence clustered data is serendipitous for users for analysis and decision making and the whole process is elucidated with examples and experimental results.